Neuropeptide Profiles of Mammalian Male Genital Tract: Distribution and Functional Relevance in Reproduction - Omirinde, Jamiu O.; Azeez, Idris A. (Frontiers in Veterinary Science, 2022)
Neuropeptides are secretory peptides characterized by small chains of amino acids linked by peptide bonds. They are majorly found in some mammalian neurons and glial cells, where they modulate a variety of physiological homeostasis. In the male genital tract, they are mostly found in the neuronal fibres supplying the vasculature, smooth muscular layer, interstitium and lamina propria of tunica mucosa of the various reproductive organs. Functionally, neuropeptides are strongly implicated in vascular temperature regulations, spermatozoa extrusion, epididymal content transportation and movement of accessory gland secretions. This review provides an overview of neuropeptides with respect to their synthesis, release, and mechanism of actions, with emphases on the locally acting neuropeptides such as the- Substance P [SP], Neuropeptide Y [NPY], vasoactive intestinal peptides [VIP], Calcitonin gene-related peptide [CGRP], galanin [GAL], cholecystokinin [CCK], C-terminal flanking peptide of NPY [CPON], peptide histidine isoleusine [PHI], met- and leu-enkephalins [M-ENK and L-ENK]) along the male genital tract (i.e., spermatic cord, testis, epididymis, ductus deferens and accessory sex organs) of fourteen (14) species of mammals and their marked influence on reproduction. This review also revealed from documented reports that the vast majority of neuropeptides present in the autonomic nerve supply to the male genital tract probably co-exist with other peptides or with various neurotransmitters (tyrosine hydroxylase, dopamine beta hydroxylase and 5-hydroxytryptamine). In addition, documented evidence of variation in age, season and intraspecies differences were identified as notable factors of influence in peptidergic nerve fibres distribution.